Simulation-based optimal design of heavy trucks by model-based decomposition: an extensive analytical target cascading case study. (7th October 2004) - Kokkolaras, M.; Louca, L.; Delagrammatikas, G.; Michelena, N.; Filipi, Z.; Papalambros, P.; Stein, J.; Assanis, D.
We present the findings of an extensive case study for the decomposed, simulation-based, optimal design of an advanced technology heavy truck by means of analytical target cascading. The use of a series hybrid-electric propulsion system, in-hub motors, and variable height suspensions is considered with the intention of improving both commercial and military design attributes according to a dual-use philosophy. Emphasis is given to fuel economy, ride, and mobility characteristics. The latter are predicted by appropriately developed analytical and simulation models. This article builds on previous work and focuses on recent efforts to refine the applied methodologies and draw final conclusions.